Teachers' Perceptions of the Kahoot Use in Learning of Pancasila and Citizenship Education (PPKN) in Public Elementary School - Ash Shodiq, Rodhatul Alawiyah; Prastowo, Andi (SITTAH: Journal of Primary Education, 2024)
This study contains issues related to 1) teachers' perceptions of the use of the Kahoot application in Civics learning at SDN Depok 1, 2) what are the advantages and disadvantages of teachers in using the Kahoot application in Civics learning, 3) how the application of Kahoot media in Civics subjects. In this study, researchers conducted surveys or interviews with teachers at SDN Depok 1 to see perceptions of using Kahoot in Civics learning. This study aims to analyze teacher perceptions of using Kahoot in Civics learning. This study uses a qualitative research approach and case study method. Data collection techniques with observation, interviews, and documentation. This research was conducted at the SDN Yogyakarta area, namely Depok 1 State Elementary School, with 28 students, 12 boys and 16 girls, and 1 class teacher. The results showed 1) the teacher's perception, in this case, is evident from the indicators of a teacher in getting a response, description, and understanding obtained when using Kahoot media in learning, 2) the advantages of Kahoot media are that it makes it easier for teachers to evaluate learning, makes it easier to see the score, while the disadvantages of using the Kahoot application according to teacher perceptions are that it requires high internet access, 3) Application of Kahoot media in Civics subjects.